(untitled) (Clinics, 2013)
OBJECTIVE: To analyze the expression of hypoxia-inducible factors (hypoxia-inducible factor 1A and hypoxia-inducible factor 2A) and aldehyde dehydrogenase proteins in patients with locally advanced breast carcinoma who were subjected to neoadjuvant chemotherapy. METHODS: We included 90 patients with histologically confirmed stage II and III breast carcinoma who were treated with neoadjuvant chemotherapy between 2000 and 2005. Immunohistochemistry for aldehyde dehydrogenase, hypoxia-inducible factor 1A, and hypoxia-inducible factor 2A was performed before and after neoadjuvant chemotherapy. We analyzed the influence of clinical and pathological features on clinical and pathological response, disease-free survival, and overall survival. RESULTS: An objective clinical response to neoadjuvant chemotherapy was observed in 80% of patients, with 12% showing a complete pathological response. Among all clinical and pathological parameters, only the expression of hypoxia-inducible factor 1A was associated with a pathological response. A positive association was found between expression of aldehyde dehydrogenase and that of hypoxia-inducible factor 1A before and after chemotherapy. Aldehyde dehydrogenase expression was associated with expression of hypoxia inducible-factor 2A in tumors after neoadjuvant treatment. In a univariate analysis, prognosis was influenced by age, pathological response, metastasis to axillary lymph nodes after neoadjuvant chemotherapy, overexpression of hypoxia-inducible factor 2, and the presence of aldehyde dehydrogenase-positive cells within the primary tumor after neoadjuvant chemotherapy. In a multivariate analysis, only age and the presence of aldehyde dehydrogenase-positive cells after chemotherapy were associated with reduced overall survival. CONCLUSION: The presence of aldehyde dehydrogenase-positive cells within the residual tumor after neoadjuvant chemotherapy is associated with an increase in the expression of hypoxia-inducible factor 2A and with poor prognosis in patients with locally advanced breast cancer.